Elite athletes’ genetic predisposition for altered risk of complex metabolic traits - Banting, Lauren K (BMC Genomics, 2015)
BACKGROUND: Genetic variants may predispose humans to elevated risk of common metabolic morbidities such as obesity and Type 2 Diabetes (T2D). Some of these variants have also been shown to influence elite athletic performance and the response to exercise training. We compared the genotype distribution of five genetic Single Nucleotide Polymorphisms (SNPs) known to be associated with obesity and obesity co-morbidities (IGF2BP2 rs4402960, LPL rs320, LPL rs328, KCJN rs5219, and MTHFR rs1801133) between athletes (all male, n = 461; endurance athletes n = 254, sprint/power athletes n = 207), and controls (all male, n = 544) in Polish and Russian samples. We also examined the association between these SNPs and the athletes’ competition level (‘elite’ and ‘national’ level). Genotypes were analysed by Single-Base Extension and Real-Time PCR. Multinomial logistic regression analyses were conducted to assess the association between genotypes and athletic status/competition level. RESULTS: IGF2BP2 rs4402960 and LPL rs320 were significantly associated with athletic status; sprint/power athletes were twice more likely to have the IGF2BP2 rs4402960 risk (T) allele compared to endurance athletes (OR = 2.11, 95% CI = 1.03-4.30, P <0.041), and non-athletic controls were significantly less likely to have the T allele compared to sprint/power athletes (OR = 0.62, 95% CI =0.43-0.89, P <0.0009). The control group was significantly more likely to have the LPL rs320 risk (G) allele compared to endurance athletes (OR = 1.26, 95% CI = 1.05-1.52, P <0.013). Hence, endurance athletes were the “protected” group being significantly (p < 0.05) less likely to have the risk allele compared to sprint/power athletes (IGF2BP2 rs4402960) and significantly (p < 0.05) less likely to have the risk allele compared to controls (LPL rs320). The other 3 SNPs did not show significant differences between the study groups. CONCLUSIONS: Male endurance athletes are less likely to have the metabolic risk alleles of IGF2BP2 rs4402960 and LPL rs320, compared to sprint/power athletes and controls, respectively. These results suggest that some SNPs across the human genome have a dual effect and may predispose endurance athletes to reduced risk of developing metabolic morbidities, whereas sprint/power athletes might be predisposed to elevated risk.